Urinary Biomarker of Prenatal Exposure to Disinfection Byproducts, Maternal Genetic Polymorphisms in CYP2E1 and GSTZ1, and Birth Outcomes - Yang, Pan; Cao, Wen-Cheng; Zhou, Bin; Zheng, Tong-Zhang; Deng, Yan-Ling; Luo, Qiong; Miao, Yu; Chen, Da; Zeng, Qiang; Lu, Wen-Qing (Environmental science & technology, 2019)
The effects of disinfection byproducts (DBPs) on adverse birth outcomes remain unsettled. Maternal genetic variants in relation to DBP metabolism may modify this effect. Pregnant women during late pregnancy (n = 1306) were included from a Chinese cohort. Maternal urinary trichloroacetic acid (TCAA) was measured as a biomarker of DBP exposure. Maternal genotyping was conducted in cytochrome P450 2E1 (CYP2E1; rs2031920, rs3813867, and rs915906) and glutathione S-transferase zeta-1 (GSTZ1; rs7975). The associations between maternal urinary TCAA and birth outcomes and statistical interactions between maternal exposure and genetic polymorphisms were estimated. We found that maternal urinary TCAA levels were associated with decreased birth weight (P for trend = 0.003) and ponderal index (P for trend = 0.004). Interaction analyses showed that maternal urinary TCAA in association with decreased birth weight was observed only among subjects with CYP2E1 rs3813867 GC/CC versus GG (P int = 0.07) and associations with decreased birth length, ponderal index, and gestational age were observed only among subjects with GSTZ1 rs7975 GA/AA versus GG (P int = 0.07, 0.02, and 0.02, respectively). Our results suggested that prenatal DBP exposure was negatively associated with birth weight and ponderal index, and maternal genetic polymorphisms in CYP2E1 and GSTZ1 might modify these associations.